Fibroblast cell therapy enhances initial healing in recessive dystrophic epidermolysis bullosa wounds: results of a randomized, vehicle‐controlled trial. (31st October 2013) - Petrof, G.; Martinez‐Queipo, M.; Mellerio, J.E.; Kemp, P.; McGrath, J.A.
Abstract : What's already known about this topic? There is a desperate need to develop new therapies for patients with recessive dystrophic epidermolysis bullosa (RDEB). Cultured fibroblasts represent a form of cell therapy that might have clinical utility in RDEB. Injecting allogeneic fibroblasts into RDEB skin has been shown to modify disease biology but whether this procedure has a beneficial impact on wound healing is not yet known. What does this study add? We assessed the effects of injecting of allogeneic fibroblasts into the margins of chronic erosions in individuals with RDEB in a prospective, double‐blind, randomized, vehicle‐controlled phase II trial. A single intradermal injection of allogeneic fibroblasts increases the initial rate of erosion healing in subjects with RDEB within the first 28 days but not thereafter. Further studies are needed to address the potential benefits of retreatment as well as optimal cell delivery. Summary: Background: Fibroblast cell therapy can modify disease biology in recessive dystrophic epidermolysis bullosa (RDEB) although whether it improves wound healing is not clear. Objective: To assess the effects of injecting of allogeneic fibroblasts into the margins of chronic erosions in individuals with RDEB in a prospective, double‐blind, randomized, vehicle‐controlled phase II trial. Methods: Erosions were randomized 1 : 1, to either a single treatment of 5 × 10 6 fibroblasts per linear cm of erosion margin or vehicle. All subjects continued standard wound care. The trial sponsor, participants and study outcome assessor were masked to treatment allocation. A hierarchy of endpoints germane to erosion closure was assessed. Results: Twenty‐six erosions in 11 subjects with RDEB were injected; 14 erosions received fibroblasts and 12 vehicle alone. A single series of injections was given at day 0 and all follow‐up visits were completed. Treatment difference between fibroblasts and vehicle was −23·5% [95% confidence interval (CI) −3·5 to −43·5, P  = 0·025] at day 7, −19·15% (95% CI 3·36 to −41·66, P  = 0·089) at day 14 and –28·83% (95% CI 7·97 to −65·63, P  = 0·11) at day 28. Beyond day 28, however, changes in mean erosion area did not differ significantly between the two groups. Conclusion: A single intradermal injection of allogeneic fibroblasts increases the initial rate of erosion healing in subjects with RDEB within the first 28 days but not thereafter. Further studies are needed to address the potential benefits of retreatment as well as optimal cell delivery.